1967
DOI: 10.1099/0022-1317-1-1-41
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Interferon on the Synthesis and Activity of an RNA Polymerase Isolated from Chick Cells Infected with Semliki Forest Virus

Abstract: SUMMARYThe effect of interferon on the activity and synthesis of a specific Semliki forest virus RNA polymerase has been studied. Highly purified and semipurified interferons were without effect on the action of the viral RNA polymerase in the in vitro assay, while crude interferon preparations were inhibitory. Polymerase activity was low in interferon-treated infected cells, but this did not result from the presence of enzyme inhibitors in the preparations. Attempts to demonstrate an inhibitor of the polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
7
0

Year Published

1967
1967
1979
1979

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 12 publications
3
7
0
Order By: Relevance
“…Thus, the inhibition of viral RNA synthesis could result from the primary inhibition of viral RNA polymerase synthesis Friedman and Sreevalsan, 1970). A similar depression of viral polymerase synthesis was found in Semliki Forest virus infection of chick cells Sonnabend et al, 1967) and in Mengovirus infection of L cells (Miner et al, 1966).…”
Section: Inhibition Of Viral Message Translation In Cells Extensive supporting
confidence: 53%
“…Thus, the inhibition of viral RNA synthesis could result from the primary inhibition of viral RNA polymerase synthesis Friedman and Sreevalsan, 1970). A similar depression of viral polymerase synthesis was found in Semliki Forest virus infection of chick cells Sonnabend et al, 1967) and in Mengovirus infection of L cells (Miner et al, 1966).…”
Section: Inhibition Of Viral Message Translation In Cells Extensive supporting
confidence: 53%
“…The results suggested that interferon blocks virus growth by inhibiting production by parental virus of the polymerase necessary for formation of the ribonuclease-resistant templates employed in the production of new viral RNA. This in turn suggested, in agreement with previous observations (1,9,10,13,16), that the mechanism for interferon action involves the inhibition of virus protein synthesis.…”
supporting
confidence: 91%
“…Levy, personal communication). In addition, during the log phase of virus growth, interferon treatment inhibits the formation of at least two virus specific proteins, the RNA polymerases of Mengo virus (13) and of Semliki forest virus (SFV) (16).…”
mentioning
confidence: 99%
“…Most of the studies with intact cells point to one of two processes as the primary targets of interferon action: (i) the transcription of early viral mRNA (2, 3, 14, 15, 25, 26, 33; M. N. Oxman, personal communication); and (ii) the translation of early viral mRNA (4,10,20,23,28,29,34,40). The inhibition of viral RNA synthesis in vitro has not yet been reported, only an accelerated degradation (27).…”
Section: Fig 1 Competition Between Mouse Globin Mrnamentioning
confidence: 99%